2021
DOI: 10.1007/s11356-021-16973-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative mapping of plant species diversity using ensemble learning algorithms combined with high accuracy surface modeling

Abstract: Plant species diversity (PSD) has always been an essential component of biodiversity and plays an important role in ecosystem functions and services. However, it is still a huge challenge to simulate the spatial distribution of PSD due to the difficulties of data acquisition and unsatisfactory performance of predicting algorithms over large areas. A surge in the number of remote sensing imagery, along with the great success of machine learning, opens new opportunities for the mapping of PSD. Therefore, differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In contrast, Wang et al (2022) used 1,620 samples obtained over 10 years, on the one hand the sample size was larger, and on the other hand the model was trained for environmental changes over a 10 year period, so the model accuracy was higher than this study. The R 2 of the optimal model in this study was 0.60, and the RMSE was 1.65 n/m 2 in the simulation of PSD; the RMSE of the RF model in Zhao et al (2022) was 1.94 n/m 2 , and the RMSE of the optimal HASM-XGBoot model reached 1.19 n/m 2 . HASM can effectively solve ecological environmental surface modeling errors, thus improving the accuracy of conventional machine learning models, we aim to test combinations of HASM methods in the future.…”
Section: Psd and Agb Inversion Model Accuracymentioning
confidence: 51%
See 1 more Smart Citation
“…In contrast, Wang et al (2022) used 1,620 samples obtained over 10 years, on the one hand the sample size was larger, and on the other hand the model was trained for environmental changes over a 10 year period, so the model accuracy was higher than this study. The R 2 of the optimal model in this study was 0.60, and the RMSE was 1.65 n/m 2 in the simulation of PSD; the RMSE of the RF model in Zhao et al (2022) was 1.94 n/m 2 , and the RMSE of the optimal HASM-XGBoot model reached 1.19 n/m 2 . HASM can effectively solve ecological environmental surface modeling errors, thus improving the accuracy of conventional machine learning models, we aim to test combinations of HASM methods in the future.…”
Section: Psd and Agb Inversion Model Accuracymentioning
confidence: 51%
“…In previous studies in which biomass has been monitored via remote sensing, several variables including vegetation indices, climate, topography, soil, and other variables have been used to increase model accuracy (Liang et al, 2016). However, few studies have integrated variables such as effective vegetation index, climate, topography, soil, and other variables into models for large-scale grassland species diversity monitoring (Choe et al, 2021;Zhao et al, 2022). In addition, some studies (Fauvel et al, 2020;Ge et al, 2022) have compared the efficacy of multiple machine learning models for modeling grassland species diversity and biomass, previous studies have shown that the random forest (RF) model is particularly effective.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR models attempt to derive the relationship between bioactivity and chemical features to predict potential inhibitors. Recently, incorporating machine learning (ML) methods, such as hyperparameter tuning [ 50 ] and ensemble methods [ 51 , 52 ] into QSAR modeling has improved the hit rate of QSAR models.…”
Section: Introductionmentioning
confidence: 99%